Porous Models for Wave-seabed Interactions - Jeng, Dong-Sheng. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
"Porous Models for Wave-seabed Interactions" discusses the Phenomenon of wave-seabed interactions, which is a vital issue for coastal and geotechnical engineers involved in the design of foundations for marine structures such as pipelines, breakwaters, platforms, etc. The most important sections of this book will be the fully detailed theoretical models of wave-seabed interaction problem, which are particularly useful for postgraduate students and junior researchers entering the discipline of marine geotechnics and offshore engineering. This book also converts the research outcomes of theoretical studies to engineering applications that will provide front-line engineers with practical and effective tools in the assessment of seabed instability in engineering design. Prof. Dong-Sheng Jeng works at Shanghai Jiao Tong University, China.